2008
DOI: 10.3414/me0523
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Assessment of a Plaque Scoring Index Using Photographs

Abstract: Summary Objectives: The need to evaluate the reliability of a clinical index before using it as a research tool is clearly recognized. Therefore the aim of this study was to evaluate whether a new calibration method by means of photographs would be useful for assessing the examiners’ reliability in the interpretation of a plaque index. Methods: Nine children were randomly recruited from a public school in Rio de Janeiro, Brazil. Two trained ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This was not possible for reasons of timing of the data collection, lack of resources to bring the dentists together from around the country, and population limitations . Other studies have shown that the use of photographs may replace clinical examination for the purposes of training and calibration when in vivo calibration is not practical, without adversely affecting data quality . However, caregivers were informed in advance of the evaluation dates, which was likely to have led to an improvement in oral hygiene at these times.…”
Section: Discussionmentioning
confidence: 99%
“…This was not possible for reasons of timing of the data collection, lack of resources to bring the dentists together from around the country, and population limitations . Other studies have shown that the use of photographs may replace clinical examination for the purposes of training and calibration when in vivo calibration is not practical, without adversely affecting data quality . However, caregivers were informed in advance of the evaluation dates, which was likely to have led to an improvement in oral hygiene at these times.…”
Section: Discussionmentioning
confidence: 99%
“…Residents who met one of these screening criteria were examined by a dentist consultant and were eligible if their oral plaque score was > 1.0. The oral plaque scoring method was adapted from published and validated plaque scoring tools (19, 20). For dentate patients (i.e., > 6 teeth), plaque was scored as follows: 0= no plaque noted, 1= plaque seen only when the tip of a probe was passed over tooth (or tissue bearing side of denture surface), 2= plaque obvious with naked eye (or visible on <50% of denture surface), 3= gross deposits of plaque over entire tooth (or on >50% of denture surface).…”
Section: Methodsmentioning
confidence: 99%
“…Initial eligibility screening for impaired oral hygiene required no documented dental examination for more than 12 months or assessment by nursing staff that oral hygiene was poor. A dentist consultant examined residents who met one of these screening criteria, and they were eligible if their oral plaque score using a scoring method adapted from published and validated plaque scoring tools 19,20 was greater than 1.0. For dentate patients (46 teeth), plaque was scored as follows: 0 5 no plaque noted, 1 5 plaque seen only when the tip of a probe was passed over tooth (or tissue-bearing side of denture surface), 2 5 plaque obvious with naked eye (or visible on o50% of denture surface), 3 5 gross deposits of plaque over entire tooth (or on 450% of denture surface).…”
Section: Inclusion and Eligibility Criteriamentioning
confidence: 99%
“…Leonardo da Vinci appraised the ratio of different facial elements, applying what he called the golden ratio . Clinical Photography, already frequently used for medical teaching purposes , is also more recently being applied as an important diagnostic and follow‐up tool in clinical medicine . Driessen et al.…”
Section: Introductionmentioning
confidence: 99%